ANALISIS BENCANA LONGSOR DI DESA KALITLAGA KABUPATEN BANJARNEGARA PROVINSI JAWA TENGAH - Nasibu, Rito (Sainstek, 2009)
Banjarnegara is one of the sub-district in Central Java (a province in Indonesia) which is located in hazardous landslide area. There are some sub district which is located in high level hazardous landslide area: Karangkobar, Banjarnegara, Banjarmangu, Kalibening, and Madukara. Meanwhile, Kalitlaga, Purwonegoro, Pagentan, Susukan and Wanayasa is located in middle level hazardous landslide area. The kind of landslide in Kalitlaga is kind of curve debris flow which caused by sand stones movement on clay stones as slippery area. It makes the clay stones can not release the water instead it becomes slippery. The land used has to be planned by the society, so the plant which has been planted is not weight on the land. Societies awareness to do not construct the artificial recharge, because it can raise the ground water level and make the land unstable. A good drainase system has to be developed to reduce water absorption. The supplies of extensometer, a tool to measure landslide have to be increased and the government is expected to fund the supplying. Government and societies role are required in landslide disaster mitigation efforts in Kalitlaga Village, Pagetan, Banjarnegara Keywords: disaster area, landslide, extensometer.